Economic Income as a Cause of Stunting: An Analysis Based on the Perspective of Karl Marx: Literature Review - Sarifudin Andi Latif; Arlin Adam; Syamsu A Kamaruddin (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Stunting begins to appear when the child is two years old and continues when the fetus is still in the womb. The increase in child morbidity and mortality is the impact caused by the incidence of stunting. Stunting children will be able to experience disturbances in their intelligence level, susceptibility to diseases, decreased productivity, and stunted economic growth, which impacts poverty. Method: This study is a Literature Review using the PRISMA method. Articles published in 2022-2024 were identified by conducting database searches (Garuda and Google Scholar) and keywords